Microhardness characteristics values of root canal dentin after application with different types of EDTA - Wahyuniwati Wahyuniwati; Juni J. Nugroho; Aries C. Trilaksana; Christine A. Rovani; Nurhayaty Natsir; Indrya K. Mattulada (Journal of Dentomaxillofacial Science, 2016)
This study aims to determine the characteristics of the microhardness impairment root canal dentin after application with different types of EDTA. Samples mandibular premolar teeth with one root canal, each divided into 4 groups: EDTA solution, EDTA gel, EDTA cream and negative control; and each group consisted of 6 samples. The teeth were decoronated  at cementoenamel junction (CEJ),  prepared by the crown down pressureless technique, cut along  longitudinal direction, and  each sample was attached  to selfcured acrylic and then soaked in distilled water. Samples were taken early microhardness measurement by means of Digital Vickers Microhardness Tester. The sample is then applied to the appropriate group of materials EDTA for 5 minutes, except for the negative control group, soaked in saline solution for 5 menit, then performed the final measurement of microhardness of dentin. The results of measurements taken from  the average value of measurements made at 3 points, coronal, middle and apical. Data were collected and analyzed using ANOVA and Tukey’s Post Hoc test.The results showed there are differences in dentin microhardness decrease significantly in all treatment groups compared to the negative control group (p <0.05) with the largest drop in the group EDTA solution, amounting to 13 667 kg / mm2. Nevertheless, based on the results of different statistical test further, discovered the value of p> 0.05 which means there is no difference in microhardness reduction in dentin significantly among the test group.